2009
DOI: 10.1021/ja901011x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Alkaline Earth Metal Dications: Effects of Metal Ion Size Determined Using Infrared Action Spectroscopy

Abstract: Infrared laser action spectroscopy is used to characterize divalent Mg, Ca, and Ba ions solvated by discrete numbers of water molecules in the gas phase. The spectra of the hexahydrated ions are very similar and indicate that all six water molecules directly solvate the metal ion. The spectra of the heptahydrated ions indicate the presence of populations of structures that have a water molecule in the outer shell for all ions and an average coordination number (CN) for Ba that is higher than that for Ca or Mg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
85
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 70 publications
13
85
0
Order By: Relevance
“…We have confirmed through a temperature study that this peak is due to a free OH bond and not involved in hydrogen bonding (SI Appendix). A free OH of interfacial water molecules with their oxygens interacting with Mg 2þ or with the Mg 2þ solvation shell likely contributes to this band (18). A peak in this spectral region was also observed by others and assigned to the symmetric stretch of the decoupled free OH and donor-bonded OH of three-coordinate water molecules (16) and weakly hydrogen-bonded water molecules (19).…”
Section: Resultssupporting
confidence: 69%
“…We have confirmed through a temperature study that this peak is due to a free OH bond and not involved in hydrogen bonding (SI Appendix). A free OH of interfacial water molecules with their oxygens interacting with Mg 2þ or with the Mg 2þ solvation shell likely contributes to this band (18). A peak in this spectral region was also observed by others and assigned to the symmetric stretch of the decoupled free OH and donor-bonded OH of three-coordinate water molecules (16) and weakly hydrogen-bonded water molecules (19).…”
Section: Resultssupporting
confidence: 69%
“…[13,14] From these experimental studies, the bond dissociation energies (BDEs) for Mg 2 + (H 2 O) x , for x = 6-14 and x = 5-10, were determined, which leaves theoretical calculations to solve the bond energies for the remaining inner-shell complexes (x = 1-4). [16] This study revealed that 6 water molecules bind directly to magnesium and that even with 32 water ligands, effects of the metal persist in influencing the structure of the outermost water molecules, which is in contrast to analogous complexes of the larger calcium and barium dications. [15] This group also investigated Mg 2 + (H 2 O) x complexes in which x = 6-32 by infrared multiple photon dissociation (IRMPD) action spectroscopy in the OH stretching region (2800-3800 cm À1 ) in a Fourier transform ion cyclotron resonance (FTICR) mass spectrometer.…”
Section: Introductionmentioning
confidence: 88%
“…In aqueous solution, the most stable hydration states for Ca 2+ are CWT = 6, 7, consistent with experimental hydration number. 38,39 The most stable bound state for Ca 2+ is at (CWT = 2, CLP = 4), where the total coordination number is 6. Other stable bound states are at CLP = 3, 4, 5 with total coordination number of 4 ∼ 6, which are 2 ∼ 4 kcal/mol higher than the global minimum (see Table 1).…”
Section: 37mentioning
confidence: 99%